Busy book as a means to build multiliteracies for children at TBM Smart Friends - Rika Pristian Rika; Chyntia Heru Woro Prastiwi; Neneng Rika Jazilatul Kholidah; Fifi Zuhriah; Sri Ningsih (Community Empowerment, 2022)
Since 2021, Trembes village has had a Smart Friends TBM (Community Reading Park) to increase village literacy. However, this TBM has fewer varied activities and programs, and the number of visitors is still low. To solve these issues, the PkM team implemented a community service program that used busy books to assist children in improving their multiliteracy competencies in the fields of economic, English, mathematics, Pancasila, and citizenship literacy. Various methods are developed, including lectures, volunteerism, questions and answers about interesting and popular themes, and demonstrations. As a result of this program, children were able to create and present busy book sheets with the themes of economic, English, mathematics, Pancasila literacy, and citizenship literacy.